Scaled Isolation of Mesenchymal Stem/Stromal Cell‐Derived Extracellular Vesicles. (21st September 2020) - Börger, Verena; Staubach, Simon; Dittrich, Robin; Stambouli, Oumaima; Giebel, Bernd
Abstract: Mesenchymal stem/stromal cells (MSCs) provide therapeutic effects in many diseases. Contrary to initial hypotheses, they act in a paracrine rather than a cellular manner. To this end, extracellular vesicles (EVs) have been found to mediate the therapeutic effects, even when harvested from MSC‐conditioned cell culture supernatants. Lacking self‐replicating activity and being so small that MSC‐EV preparations can be sterilized by filtration, EVs provide several advantages as therapeutic agents over cellular therapeutics. At present, methods allowing EV preparation from larger volumes are scarce and regularly require special equipment. We have developed a polyethylene glycol−based precipitation protocol allowing extraction of EVs from several liters of conditioned medium. MSC‐EVs prepared with this method have been successfully applied to a human graft‐versus‐host disease patient and to several animal models. Although the method comes with its own limitations, it is extremely helpful for the initial evaluation of EV‐based therapeutic approaches. Here, we introduce the technique in detail and discuss all critical steps. © 2020 The Authors. Basic Protocol 1 : Preparation of MSC‐conditioned medium for scaled MSC‐EV production Basic Protocol 2 : PEG precipitation OF MSC‐EV from MSC‐conditioned medium